2008
DOI: 10.1007/s10535-008-0090-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of phosphomannose isomerase-based selection system for Agrobacterium-mediated transformation of tomato and potato

Abstract: Two selection systems for Agrobacterium tumefaciens mediated transformation of tomato and potato were compared. In the tomato (Lycopersicon esculentum cv. Moneymaker), the highest transformation rate, 4.2 %, of cotyledon explants on mannose-selection medium was obtained when mannose/sucrose concentration in the regeneration medium was 5/15 g dm -3 . The best transformation efficacy with the commonly used concentration of 100 mg dm -3 kanamycin as a selection agent was 9 %. In the potato (Solanum tuberosum cv. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…This system is influenced by a number of factors such as bacterial strains, plasmids, tissue culture environment, media for explant culture, co-cultivation duration, acetosyringone (AS), explant wounding, selective marker and vector and competency of target plant tissues for infection (Li et al 1997, Salas et al 2001, Zambre et al 2003, Yu et al 2002, Olhoft et al 2003, Wu et al 2003, Cheng et al 2004, Bříza et al 2008, Cho et al 2008. Unlike the role of bacterial factors, the host factors in transformation process has remained obscure for nearly a century, and only recently have we begun to understand how Agrobacterium hijacks host factors and cellular processes during transformation process , Lacroix et al 2005, Tao et al 2004, Zhu et al 2003, Roberts et al 2003, Ditt et al 2006, Anand et al 2007, Loyter et al 2005, Baek and Shapleigh 2005.…”
Section: Introductionmentioning
confidence: 99%
“…This system is influenced by a number of factors such as bacterial strains, plasmids, tissue culture environment, media for explant culture, co-cultivation duration, acetosyringone (AS), explant wounding, selective marker and vector and competency of target plant tissues for infection (Li et al 1997, Salas et al 2001, Zambre et al 2003, Yu et al 2002, Olhoft et al 2003, Wu et al 2003, Cheng et al 2004, Bříza et al 2008, Cho et al 2008. Unlike the role of bacterial factors, the host factors in transformation process has remained obscure for nearly a century, and only recently have we begun to understand how Agrobacterium hijacks host factors and cellular processes during transformation process , Lacroix et al 2005, Tao et al 2004, Zhu et al 2003, Roberts et al 2003, Ditt et al 2006, Anand et al 2007, Loyter et al 2005, Baek and Shapleigh 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of phenolic compounds, acetosyringone to the co-cultivation has also been reported to increase the transformation frequency (Katia et al 1993, Cortina andCulianez-Macia 2004). Moreover, different selection markers such as bar gene and phosphomannose isomerase (pmi) gene has also been used for increasing the transformation efficiency of tomato and other important vegetable crops (Cho et al 2008, Bříza et al 2008.…”
mentioning
confidence: 99%
“…Most initial transformation studies in tomato used neomycin phosphotransferase ( NPT II conferring resistance to kanamycin) and GUS as reporter genes to establish adequate protocols (Table 1). In later studies, other genes such as hygromycin phosphotransferase ( HPT ) gene (Chaudhry and Rashid, 2010), bialaphos resistance ( bar ) gene (Abu‐El‐Heba et al, 2008; Khoudi et al, 2009), and phosphomannose isomerase ( pmi ) gene (Briza et al, 2008) have also been used for optimizing transformation in tomato. For removal of Agrobacterium contamination during subculture of transgenic tissues and shoots, cefotaxime has been most commonly used, although it has also been reported that ticarcillin/potassium clavulanate was superior for removing Agrobacterium contamination and enhancing transformation (Ling et al, 1998).…”
Section: Strategies Employed To Enhance Abiotic Stress Tolerance In Tmentioning
confidence: 99%